The role of internal control in supporting the effectiveness of the credit system for small and medium enterprises (Case Study at Bank Rakyat Indonesia Cirebon Coastal Unit) - Anggie giselalutfi (Institute of Accounting Research and Novation (IARN), 2021)
Summary of credit is the main activity in the BRI unit Pesisir. Security problems is a credit problem that must be observed, because of the risks that may arise in the credit system and will likely lead to a jammed credit given to customers that reflect the operational viability of the bank. Adequate internal control that are closely tied to the effectiveness of the credit for the system of internal control that are not adequately applied also influence the effectiveness of the credit system. The author of the research system of the BRI unit Pesisir. Goal of this research to examine how the effectiveness of the implementation of internal control, the mechanism how the credit system, and how the role of internal control system effectiveness in supporting the credit of UKM. Results of research conducted, the author obtained a description of activities and implementation of internal control effectiveness of the credit system in the BRI unit Pesisir. In conducting activities, BRI unit Pesisir has implemented internal control which include: Environmental Control, Risk assessment, Control Summary, Information and Communication, and Monitoring. Authors concluded based on that research and discussion of the internal control unit on the BRI Pesisir a role in supporting the effectiveness of the credit system.9 pt).